Influences of Insurgency on Service Delivery of Child Development Centers in the Three Southernmost Provinces of Thailand - Dongnadeng, Hasan Akrim; Ismail, Mazlan (Journal of Social Sciences and Humanities Research in Asia, 2018)
The three southernmost provinces of Thailand are most disrupted by insurgency. However, there had been no empirical evidences which particularly addressed its influences on service delivery of child development centers in the area. This research aimed to investigate such influences on service delivery of child development centers in selected municipalities of the three provinces. The qualitative approach was utilized in interviewing nine key informants, derived from purposive sampling. The results revealed that the insurgency influenced the quality of learning and care by disrupting learning activities and process, interrupting process of providing care for children, and diminishing parents’ trust and acceptance of service delivery. Insurgency also influenced the staff’s potential by changing their behavior in delivering services, disrupting their opportunities in improving knowledge and skills. Accumulated fears caused the staff to lose motivation in delivering service to customers. Nevertheless, the study found that regarding the element of customer focus the insurgency did not hamper the interaction between the staff and parents. In fact, they developed better relationship and collaboration. According to most informants, the insurgency did not influence the centers’ responses to the parents’ needs and feedbacks. However, there were some problems pertaining to cultural sensitivity in the insurgent area. The study recommends that the Thai government and related organizations prepare alternative plans for carrying out learning activities and learning process, pay more attention to security of children and staff, focus on staff’s career advancement and maintenance of workforce, as well as raise awareness of sensitive issues in the conflict zone.